Lifestyle Modification Practice and Associated Factors Among Diagnosed Hypertensive Patients in Selected Hospitals in Central Gondar Zone. (March 2022) - Smachew, Moges; Melak, Melkitu Fentie; Atenafu, Azeb; Belew, Aysheshim Kassahun
Background: Hypertension is one of the leading causes of disability and death in both developed and developing countries including Ethiopia. Non-communicable diseases account for 42% of deaths in Ethiopia. However, it is still widely undetected and poorly controlled. Hence, this study aims to assess the lifestyle modification practices and related factors of adult hypertensive patients in the central Gondar region of northwestern Ethiopia. Methods: Institutional based, cross-sectional study was conducted from April 10 up to May 10, 2021. A simple random sampling was used to select 629 study participants. Data were collected by using self-administered and structured questionnaire. Data were entered to EpiData 4.6 and exported to SPSS 20 for further analysis. A multivariable logistic regression analysis was employed to identify the factors associated with lifestyle modification. Adjusted Odds Ratio (AOR) with 95% confidence interval was used to show the strength of association, while a P-value <.05 of was used to declare the significance of association. Results: The overall prevalence of recommended lifestyle modification in hypertensive patients was 24.2% (95% CI (20.8, 27.5)). Age ⩾65 years (AOR = 0.59, 95% CI: 0.39, 0.88), no formal education (AOR = 0.65, 95% CI: 0.4, 0.97), diagnosis time is 5 to 10 years (AOR = 1.93, 95% CI: 1.11, 3.34), co morbidities (AOR = 0.47, 95% CI: 0.3, 0.73), and rich wealth index (AOR = 1.99, 95% CI: 1.22, 3.27) are is significantly associated with good lifestyle modification practices. Conclusions: The practice of good lifestyle modifications in the study area was found to be low among the hypertensive patients. Respondents' age, education status, wealth index, duration of diagnosis, and co morbidities were found to be significant factors related to good lifestyle modification practices. Therefore, more attention should be paid to providing nutrition counseling and health promotion to improve the practice of lifestyle modification in patients with hypertension.